2018
DOI: 10.1111/bjet.12690
|View full text |Cite
|
Sign up to set email alerts
|

An IRS‐facilitated collective issue‐quest approach to enhancing students’ learning achievement, self‐regulation and collective efficacy in flipped classrooms

Abstract: Flipped classrooms have been recognized as a potential approach that enables students to have flexible time to learn before the class as well as more opportunities to apply knowledge and to interact with peers and the teacher in the class. On the other hand, researchers have pointed out the challenge of engaging students in self‐regulated learning and active participation in flipped classrooms. In this study, an Instant Response System (IRS)‐facilitated collective issue‐quest strategy is proposed for engaging … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 65 publications
1
18
0
Order By: Relevance
“…Findings of the empirical study shows that the learning achievement, self-regulation, self-efficacy and satisfaction of the students who used with the proposed IRS system were significantly better than the students that used the conventional flipped classroom approach. Moreover, in the "environment," "task strategies" and "help seeking" dimensions of self-regulation, the former had significantly higher ratings than the latter [35]. One of the most common approaches that blended learning considered in promoting and improving students online help-seeking initiatives is International Journal of Information and Education Technology, Vol.…”
Section: B What Supports Have Been Proposed To Improve Self-regulatimentioning
confidence: 99%
See 1 more Smart Citation
“…Findings of the empirical study shows that the learning achievement, self-regulation, self-efficacy and satisfaction of the students who used with the proposed IRS system were significantly better than the students that used the conventional flipped classroom approach. Moreover, in the "environment," "task strategies" and "help seeking" dimensions of self-regulation, the former had significantly higher ratings than the latter [35]. One of the most common approaches that blended learning considered in promoting and improving students online help-seeking initiatives is International Journal of Information and Education Technology, Vol.…”
Section: B What Supports Have Been Proposed To Improve Self-regulatimentioning
confidence: 99%
“…[34] Self-regulation Technology that uses planned instructional strategies with sustainable support for self-regulation [39] Self-regulation Improving self-regulation through the use of learning analytics which supports students in identifying strategies that can increase their academic performance. [35] Self-regulation Using instant response system (IRS)-facilitated collective issue-quest strategy to engage improve student's self-regulation initiatives in flipped classrooms [38] Online help-seeking Online help-seeking system called 'EchoLu' based on four design principles: Student's alertness of teacher support, promotion of social support, student's needs of privacy in help seeking, improvement of observability peers' help seeking activities [36] Online help-seeking Using online discussion board for offering instant help [37] Online help-seeking Using online discussion board for offering instant help [40] Online help-seeking The use of an Intelligent Tutoring System (ITS) for supporting students in programming tasks…”
Section: B What Supports Have Been Proposed To Improve Self-regulatimentioning
confidence: 99%
“…Also, Krabill (2015) reported the benefit of keeping students' anonymity and encouraging them to speak up in class through SRS, so that their responses reflected a more representative distribution of students' voices. Finally, Chen and Hwang (2018) showed that the use of SRSs in flipped classrooms can help to engage students in active and self-regulated learning, and enhance their collective efficacy, satisfaction and learning achievements.…”
Section: Student Response Systemmentioning
confidence: 99%
“…Likewise, [69] found that problem-based learning activities in FC have a positive effect on students' goal setting. However, the study by [70] and [71] showed insignificant differences between the experimental and control groups in the aspect of goal setting. On the other hand, students engaged in SRL prompt conditions showed a higher mean score in strategic planning [72].…”
Section: Adaptive-defensivementioning
confidence: 89%
“…Besides that, a few studies showed positive outcomes in the regulation of time management [74][68] [69]. In contrast, several studies found no significant difference in their time management strategies when compared with the control group [70][71] [75]. Moreover, [1] found that time management skills were negatively associated with Year 1 medical student learning outcomes, while positively towards Year 2 students.…”
Section: Adaptive-defensivementioning
confidence: 99%